6-Fluoro-4-oxo-4H-chromene-3-carbaldehyde - Yoshinobu Ishikawa (Acta Crystallographica Section E, 2014)
In the title compound, C10H5FO3, the non-H atoms are essentially coplanar (r.m.s. deviation = 0.0071 Å), with the largest deviation from the mean plane [0.0203 (15) Å] being found for the ring C atom in the 2-position. In the crystal, molecules are linked into a three-dimensional architecture via C—H...O hydrogen bonds and π–π stacking interactions between the chromone units along the a-axis direction [centroid–centroid distance between the benzene and pyran rings = 3.707 (2) Å].